The Relationship between Iranian EFL Teachers’ Emotional Intelligence and their Teaching Style - Ayatollahi, Mohammad Ali; Ferdosi, Fatemeh (Vision: Journal for Language and Foreign Language Learning, 2021)
The present study aimed to detect and compare the most preferred teaching styles by Iranian English teachers in public schools and private language institutes and investigate the possible relationship between EFL teachers’ teaching styles and aspects of their emotional intelligence.  The participants were 100 EFL teachers from public schools and private language institutes in Iran, Shiraz. The Persian version of the Bar-On Emotional Quotient Inventory and Grasha’s Style Inventory (TSI) was used to measure the teachers’ emotional intelligence and teaching styles, respectively. Concerning teaching style preference, formal authority style for EFL teachers of schools and facilitator style for teachers of the private institute was the most preferred styles. In addition, the least preferred styles were ‘delegator’ and ‘formal authority’ styles for public school teachers and private institute teachers, respectively. Regarding emotional intelligence, the lowest mean scores were observed in the Stress Management dimension, and the highest was related to the General Mood dimension. Furthermore, ‘general mood’, as a dimension of emotional intelligence, was highly correlated with ‘formal authority’ and ‘expert style’, both of which were public school teachers’ preferred styles. Public School teachers were relatively weak at using ‘personal model’, ‘facilitator’, and ‘delegator’ teaching styles. Thus, it is recommended that they adapt themselves to these styles.